Stylistic transformations of the actor's performance in contemporary global experiences (Al-Academy, 2025)
The process of establishing successful theatrical performances is an artistic achievement based on the dialectic of compatibility or contrast between the literary production and the structure of the theatrical performance. The process of transforming literary words (theatrical text) into a complex (kinetic formation) (audio-visual) remains different from one theatrical director to another. Since the main element in the theatrical performance is the actor. The researcher was able to divide his research into four chapters. The first chapter is the research methodology. The researcher shed light and focused on the research problem and the need for it, and through study and scrutiny he arrived at the formulation of the following question. Stylistic transformations of the actor’s performance in contemporary global experiences? Then he touched on the importance of the research, the objectives of the research, the limits of the research, and the definition of terminology and the limits of the research that was limited to the years (1972 - 2022). As for the second chapter (theoretical framework) (methods of acting in delusional and non-delusional theatre), the chapter was divided into two sections, the second section (contemporary performance experiences), and then the researcher arrived at the indicators produced by the theoretical framework.The third chapter of the research was devoted to the research procedures represented by the research population, the research sample, the research tool, the research methodology, and the sample analysis of the play (Abu al-Tayyib al-Mutanabbi), and then the fourth chapter was devoted to (the results of the sample analysis) and the conclusions as well as the recommendations.